2017
DOI: 10.1055/s-0037-1607196
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience with a Novel System of Facet Fixation to Treat Patients with Lumbar Degenerative Disease. A New Perspective in Minimally Invasive Spine Surgery?

Abstract: Facet Wedge allows facet fixation in lumbar degenerative microinstability. To the best of our knowledge, this is the first clinical series reported in the literature on this novel device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…38,[43][44][45][46][47] A few studies in this review presents a definition including facet effusion and facet angle as parameters. 22,36,48,49 The studies are published within the last decade. Signs of instability on MRI are subject of investigation and results indicate that facet effusion sign, sagittal facet angles, disc height and facet tropism might be linked to instability.…”
Section: Discussionmentioning
confidence: 99%
“…38,[43][44][45][46][47] A few studies in this review presents a definition including facet effusion and facet angle as parameters. 22,36,48,49 The studies are published within the last decade. Signs of instability on MRI are subject of investigation and results indicate that facet effusion sign, sagittal facet angles, disc height and facet tropism might be linked to instability.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Francaviglia et al . [ 28 ] recruited 38 patients affected by herniated disk, spinal canal and foraminal stenosis, and Meyerding grade I degenerative spondylolisthesis to evaluate the safety and efficacy of FW and found that low back VAS score and ODI decreased significantly after surgery. Moreover, in neuroimaging follow-up slippage or signs of adjacent segment degeneration were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…За это время были зарегистрированы осложнения у 3 пациентов: у 2 -тромбоз глубоких вен нижних конечностей, у 1 -инфекция глубоких мягких тканей, что потребовало хирургического вмешательства. По данным рентгенологических исследований не выявлено каких-либо осложнений, связанных с не-стабильностью или поломкой металлоимплантатов [16]. Обобщенные данные вышеуказанных исследований представлены в таблице.…”
Section: материалы и методыunclassified